Uma francófila na Paraíba : ressignificando a trajetória de Alaíde Chianca a partir de seu acervo pessoal - Gomes, Thiago Alves (2023)
This research focused primarily on the dissemination of the memory of Alaíde Chianca, a woman who devoted her life to nurturing and spreading the French language in the state of Paraíba, Brazil. The study enabled a recontextualization of Professor Chianca's life journey through the exploration of her personal archives. In this process, significant memories emerged of a pioneer in teaching the French language and culture in João Pessoa. The proposed research, which engaged in dialogue with the fields of information, heritage, and memory, was conducted during the COVID-19 pandemic, prior to Alaíde's passing at the age of 103 in May 2022. For this research, various documents and personal objects belonging to Alaíde were selected to help narrate her life story, including her decorations, awards, and completed works. The focus of this work was directed towards filling the information gap about the aforementioned educator, while simultaneously highlighting the significance of her memories for the Francophone community in João Pessoa.